How dynamic is organic? Spatial analysis of adopting new trends in Croatian agriculture. (December 2020) - Blaće, Ante; Čuka, Anica; Šiljković, Željka
Highlights: Croatia is among the fastest-growing EU countries in terms of organic farming area. The correlation between social variables and organically farmed areas is low. Spatial analysis revealed four clusters in Croatia (two high- and two low-value). Lifestyle is the main driving force behind the increasing number of organic farms. Abstract: The preservation of biodiversity, improving human health and the development of rural areas through organic farming are among the main aims of EU and worldwide agricultural policies. This paper discusses influential factors and the dynamics of developing organic agriculture in Croatia. The main aim of the research was to determine the connection between specific socio-economic variables and spatial patterns, showing the concentration and increase in organic production. The methodology used in the research included a quantitative analysis at the level of the 556 municipalities covering various socio-economic indicators, which were then correlated with the data on farm sizes. A hot spot analysis was performed to determine high and low clustering. The results showed low but statistically significant correlation between dependent and independent variables. However, they did not indicate any prevalent reasons for the occurrence of organic farming. Qualitative research, which included the attitude of organic farmers towards organic production, was also conducted. The qualitative study results showed that the main reason for going over to organic farming was lifestyle-related, and is the principal driving force behind the significantly increased dynamics of organic agriculture development in Croatia.